2013
DOI: 10.1503/jpn.120152
|View full text |Cite
|
Sign up to set email alerts
|

Reversal deficits in individuals with psychopathy in explicit but not implicit learning conditions

Abstract: IntroductionOur ability to learn associations between events with rewarding or punishing outcomes plays an important role in guiding our behaviour.1 Of equal importance is our capacity to successfully alter established associations to maximize performance when the environment requires us to change our behaviour. When an event that previously led to reward (event A) currently leads to punishment and when a previously punished event (event B) now yields a reward, the optimal behaviour would be to reverse the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 35 publications
4
49
0
Order By: Relevance
“…without being aff ected by contextual factors, such as task parameters. 10 The intact behavioural performance combined with aberrant brain activation reported, however, might refl ect the diff ering developmental pathways for antisocial personality disorder with and without psychopathy. The distinction between these two subgroups resembles that between troubled youths with high levels of callous-unemotional traits and those predominantly with con duct disorder, pinpointing the presence of develop mental components.…”
Section: Considering New Insights Into Antisociality and Psychopathymentioning
confidence: 97%
“…without being aff ected by contextual factors, such as task parameters. 10 The intact behavioural performance combined with aberrant brain activation reported, however, might refl ect the diff ering developmental pathways for antisocial personality disorder with and without psychopathy. The distinction between these two subgroups resembles that between troubled youths with high levels of callous-unemotional traits and those predominantly with con duct disorder, pinpointing the presence of develop mental components.…”
Section: Considering New Insights Into Antisociality and Psychopathymentioning
confidence: 97%
“…While some researchers have linked psychopathy to specific cognitive dysfunctions, such as attentional processing (e.g., Baskin-Sommers et al, 2012) and reversal learning (e.g., Budhani et al, 2006;Brazil et al, 2013), in recent years there has been a growing interest in a broader range of cognitive functions, often denoted with the umbrella-term 'executive functioning' (EF) (see De Brito & Hodgins, 2009, for an overview).…”
Section: Psychopathy and Executive Functioningmentioning
confidence: 99%
“…13 In behavioural studies off enders with antisocial personality disorder and psychopathy have shown notable impairment in using reinforcement information when choosing between punished and rewarded objects in passive avoidance, 14 extinction, 15 and reversal learning tasks. 11,16,17 The failure to use punishment information to signal inappropriate behaviour is thought to be the primary defi cit in psychopathy, and emerges early in childhood. 18 Reversal learning tasks examine the ability to adjust behaviour to changes in reinforcement contingency.…”
Section: Introductionmentioning
confidence: 99%